Antioxidative effect of Assam Tea (Camellia sinesis Var. Assamica) extract on rice bran oil and its application in breakfast cereal - Niramon Utama-ang (2018)
© 2016 Elsevier Ltd The objectives of this research were to investigate the antioxidant effect of Assam tea extract (ATE) and whether it is fit to utilise ATE by fortification in rice bran breakfast cereal (RBC). The increasing ATE powder from 0.1 to 0.3 mg/g affected to be decreased. The ATE powder at 0.3 mg/g was proved to have decreased the hexanal content (0.21 μg/ml) and thiobarbituric acid reactive substances (TBARS) (2.56 μg/g) within 28 days, and provided the highest antioxidant ability (EC50) (2481.44 mg/kg). The fortified 0.3 mg/g of ATE powder showed that increasing ATE significantly increased the total phenolic content and decreased TBARS and EC50 of breakfast cereal (p < 0.05). The suitable amount ATE powder added in RBC was 0.5%. The consumer acceptance (n = 200) of final product showed the sensory scores in the range of 6.3–6.8, with the percentages of acceptance and purchase intention at 98.0% and 89.0%, respectively.